Morphological variations in malleus among the male and female - Azam Khattak, Mariya; Usmani, Ambreen; Aslam, Sohail; Khaliq, Saneed; Ayesha Mehwish; Ahmed, Rida Rubab (Journal of the Pakistan Medical Association, 2023)
Objective: To determine gender-based morphological variations in malleus. Method: The cross-sectional descriptive study was conducted at the Ear-Nose-Throat and Radiology departments of a public-sector hospital in Karachi, from January 20 to July 23, 2021, and comprised subjects of either gender aged 10-51 years who had intact ear ossicles. They were divided into equal male and female groups. After history and a thorough examination of the ear, high-resolution computed tomography scan of petrous temporal bone was done. The images were studied for malleus, to measure the parameters of its head width, length and shape of manubrium, and total length of malleus for possible morphological variations along gender lines. Data was analysed using SPSS 23. Results: Of the 50 subjects, 25(50%) were males with mean width of the head 3.04±0.34mm, mean length of manubrium 4.47±0.48mm, and mean total length of malleus 7.76±0.60mm. The corresponding values in 25(50%) females were 3.00±0.28mm, 4.31±0.45mm and 7.41±0.51mm. The total length of malleus between both genders was significantly different (p= 0.031). The shape of manubrium was straight in 10(40%) males and 8(32%) females, and curved in 15(60%) males and 17(68%) females. Conclusion: Width of head, length of manubrium and total length of malleus were different in gender terms, but the total length of malleus was significantly different. Key Words: Ear, Malleus, Computed tomography.